EXPLORING LEXICAL AND METRICAL STRESS IN MAYA ANGELOU'S POEM ENTITLED 'STILL I RISE': A PHONOLOGICAL ANALYSIS PERSPECTIVE - Putri Khumaeroh; Syahfitri Purnama (INFERENCE: Journal of English Language Teaching, 2020)
This study deals with phonological analysis, which focuses on analyzing lexical and metrical stress in Maya Angelou's poem entitled 'Still I Rise.' This study explores the lexical stress and metrical stress used in Angelou's poem, which answers the research questions. This method is the qualitative method which means the data was written text. The writer intends to determine what lexical stress (primary and secondary stress) and metrical stress (iamb, trochee, and dactyl) are in the poem text. This research showed that lexical stress, namely primary stress with total numbers, is 43 items, and secondary stress with total numbers is three items. Also, there are metrical stresses, including iamb with nine items, trochee 27 items, and dactyl seven items.